Namibian teachers’ perceptions and practices of teaching mapwork (The Journal of Geography Education in Africa, 2021)
This article addresses the problem of consistently poor learner performance in mapwork in secondary school geography in Namibia from the perspective of teachers. It presents the findings of a qualitative case study focused on understanding geography teachers’ perceptions and pedagogical practices of mapwork. Data were generated through a questionnaire administered to thirty teachers in fifteen secondary schools in the Ohangwena Region of Northern Namibia, and interviews and classroom observations were done with a purposive sample of three teachers. The study draws on Shulman’s ideas of teachers’ pedagogical content knowledge (1986, 1987) to interpret what the three teachers say about the teaching of mapwork and how they teach it. The findings reveal that the teachers are conscientious but ill-equipped to teach mapwork. Their classroom practices focus on teaching discrete map skills and procedural knowledge with little if any, attention given to spatial conceptual understanding and application of knowledge to solve problems. The study provides insights that may be of value to teachers, teacher educators and Senior Education Officers in Namibia and other southern African contexts when addressing the problem of low learning outcomes in mapwork.